2022
DOI: 10.3390/ijerph192013469
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Frailty Phenotype and Arterial Stiffness in Older Adults Free of Cardiovascular Diseases

Abstract: Purpose: Arterial stiffness is a subclinical marker of cardiovascular disease (CVD). The pre-frailty phenotype is associated with a higher risk for CVD. This study investigated the association between the pre-frailty phenotype and arterial stiffness in community-dwelling older adults without diagnosed CVD. Methods: In total, 249 community-dwelling older adults aged 60–80 years were included in this cross-sectional study. The pre-frailty phenotype was defined by the standardized Fried criteria (muscle weakness;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…For instance, in a study conducted by Kannegieter [35] et al on the association between frailty and mobility, handgrip strength, and aortic stiffness, although possible confounders were identified, no specific methods were applied to address them, such as matching or stratifying participants or utilizing multivariate regression analysis. This limitation was also observed in similar studies conducted by Macedo [18] and Mone [29].…”
Section: Characteristics Of the Included Studiessupporting
confidence: 69%
See 3 more Smart Citations
“…For instance, in a study conducted by Kannegieter [35] et al on the association between frailty and mobility, handgrip strength, and aortic stiffness, although possible confounders were identified, no specific methods were applied to address them, such as matching or stratifying participants or utilizing multivariate regression analysis. This limitation was also observed in similar studies conducted by Macedo [18] and Mone [29].…”
Section: Characteristics Of the Included Studiessupporting
confidence: 69%
“…The methods used to measure vascular endothelial function and physical fragility were inconsistent across the included studies, with some studies using multiple measures. Of the 29 studies included in the review, carotid intima-media thickness (CIMT; n = 7 [22,26,28,33,[36][37][38]), the ankle-brachial pressure index (ABPI; n = 4 [22,36,37,45]), carotid-femoral pulse wave velocity (cfPWV; n = 7 [25,[36][37][38]41,44,45]), ankle-brachial pulse wave velocity (baPWV; n = 4 [20,21,26,32]), carotid distensibility (CD; n = 3 [36][37][38]), nitrite/nitric oxide (NO; n = 2 [23,31]), flow-mediated brachial dilatation (FMD; n = 2 [19,32]), the reactive hyperaemia index (RHI; n = 2 [34,38]), blood pressure complexity (n = 2 [20,21]), the heart-ankle vascular index (CAVI; n = 3 [22,26,27]), aortic pulse wave velocity (aPWV; n = 2 [18,35]), the aortic augmentation index (aAIx; n = 1 [38]), asymmetric dimethylarginine (ADMA; n = 1 [40]), homocysteine (Hcy; n = 2 [24,39]), the von Willebrand factor (vWF; n = 1…”
Section: Measurement Of the Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Per manufacturer’s instructions, four measurements were collected with intervals of 1-min being the first used to calibrate the device, and the average of the following 3 used as aPWV in m/s. Recent investigations have shown that the aPWV assessment used in the present study is associated with steps per day ( Cabral et al, 2021 ) and frailty ( Macêdo et al, 2022 ) in older adults.…”
Section: Methodsmentioning
confidence: 85%